Embedding accessibility and usability: considerations for e-learning research and development projects - Martyn Cooper; Chetz Colwell; Anne Jelfs (Association for Learning Technology, 2007)
This paper makes the case that if e-learning research and development projects are to be successfully adopted in real-world teaching and learning contexts, then they must effectively address accessibility and usability issues; and that these need to be integrated throughout the project. As such, accessibility and usability issues need to be made explicit in project documentation, along with allocation of appropriate resources and time. We argue that accessibility and usability are intrinsically inter-linked. An integrated accessibility and usability evaluation methodology that we have developed is presented and discussed. The paper draws on a series of mini-case studies from e-learning projects undertaken over the past 10 years at the Open University.